2010
DOI: 10.1177/0148607110362583
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Optimization of Surgical Care Shows Beneficial Outcome in Gastrectomy Surgery

Abstract: Optimization of care in gastrectomy can shorten postoperative hospital stay and provides multiple beneficial outcomes, including hastening the return of gut function, without increasing morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 35 publications
1
76
0
2
Order By: Relevance
“…Several small randomised controlled trials (RCTs) [11][12][13][14][15][16][17] and retrospective studies 18,19 have documented the benefits and safety of FTS programme implementation in patients with gastric cancer undergoing gastrectomy. Conversely, other retrospective studies 20,21 have questioned these assertions and use of the FTS pathway in this patient group has not been systematically reviewed.…”
mentioning
confidence: 99%
“…Several small randomised controlled trials (RCTs) [11][12][13][14][15][16][17] and retrospective studies 18,19 have documented the benefits and safety of FTS programme implementation in patients with gastric cancer undergoing gastrectomy. Conversely, other retrospective studies 20,21 have questioned these assertions and use of the FTS pathway in this patient group has not been systematically reviewed.…”
mentioning
confidence: 99%
“…12 Satisfaction and improved quality of life related to this treatment course have also been reported in patients undergoing gynaecological 30 and hepatic 31 surgery.…”
Section: Ftsmentioning
confidence: 67%
“…Several studies have reported experience with oesophageal resection [12][13][14][15][16] and gastric resection [17][18][19][20][21] but reports of a unit's experience with both are rarer. 22 Laparoscopic surgery was undertaken in some studies [19][20][21] whereas others examined open surgery only.…”
Section: 11mentioning
confidence: 99%
“…12,[14][15][16][17] Variations in perioperative management included use of epidural analgesia, 12,13,15,17,20,23 the role of jejunal feeding [12][13][14]16 with most opting for early enteral feeding [12][13][14][15][16] and avoidance or early removal of drains. [12][13][14][15][16][17][18][19][20][21] Radiological contrast studies were undertaken in the majority of studies 12,14,15,19,22 although they were not used in all. [16][17][18] Complication rates varied, ranging from 7% to 45%.…”
Section: 11mentioning
confidence: 99%
See 1 more Smart Citation